Socio-Demographic Profile Of Psychoactive Substance Users Attending a Centre For Mental Health, Rupandehi - Dhungana, M.; Thapa, M.; Thapa, D. (Journal of Psychiatrists' Association of Nepal, 2018)
Introduction: Psychoactive substance use is known since the origin of mankind and has been global problem that is influenced by social, economic, political and psychosocial factors. The menace of psychoactive substance abuse is that it is not only a socially unacceptable reality but in itself a disorder and is emerging as a major public health burden. Material and Method: A descriptive study was carried out with the view to find out the prevalence of psychoactive substance disorder in de-addiction unit at Centre for Mental Health (Chautari Nepal Health Foundation) in Rupandehi district of province-5, Nepal. All patients who were admitted during the study period with psychoactive substance use Disorder were interviewed by using semi structured performa for addiction. Total 387 patients with psychoactive substance dependence (according ICD-10) were enrolled in the study after providing written informed consent. The data was analyzed by using descriptive and inferential statistics with SPSS software version 16. Results: Among 387 psychoactive substance users, majority of them (34.1%) were in the age group 35 years and above, 57.1% were belonged to Brahmin/ Chhetri ethnic group. Greater proportion 44.4% of psychoactive substance abuser had started taking the drugs between the age of 16-20 years of age. Alcohol was most commonly used psychoactive substance as 47.5% were dependent to alcohol. Conclusion: Based on the study findings, it is concluded that addiction is a global burden. Youth is a vulnerable group. Therefore, special attention, Psycho education related to psychoactive substance should be started before adolescent.